Cover Feature: The Missing Parent Compound [(C5H5)Fe(η5‐P5)]: Synthesis, Characterization, Coordination Behavior and Encapsulation (Chem. Eur. J. 27/2021). Issue 27 (22nd April 2021) - Heinl, Claudia; Peresypkina, Eugenia; Balázs, Gábor; Mädl, Eric; Virovets, Alexander V.; Scheer, Manfred
Abstract : The discovery of parent pentaphosphaferrocene [CpFe(η 5 ‐P5 )] has been achieved after more than 30 years, closing the gap within the large class of pentaphosphaferrocenes; the cover image depicts the parent compound taking its proper place on the family tree. The influence of the unsubstituted Cp ligand on the complex formation was shown, reflecting specific conditions during the synthesis, its eclipsed conformation, different coordination behavior towards Cu I halides and ability to template the construction of nano‐sized fullerene‐like spheres, acting hereby, in contrast to the other homologous, as an electron donor. More information can be found in the Full Paper by M. Scheer et al. (DOI: 10.1002/chem.202100203 ).